SOCIAL MEDIA'S IMPACT ON CARDIGAN SHOPPING: TRUST, CONNECTION, AND QUALITY MATTER - Aditya Yudanegara (EKUITAS (Jurnal Ekonomi dan Keuangan), 2024)
This study aims to analyze the effect of social media interaction on cardigan purchase behavior, with a specific focus on customer relationship management, purchasing intentions, and brand engagement. The study employs a quantitative methodology, gathering data from Instagram users aged 18 to 25 in the West Java Region who are acquainted with the Sweater Vest 'Cardigan' brand. The review employs a purposive sample of 220 respondents and uses the Likert scale survey. The investigation used the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, which was specifically chosen due to the complex models and few samples. The findings reveal that virtual entertainment collaboration significantly influences sources of credibility, sources of homophily, and content quality, ultimately impacting purchase intention and behavioral engagement. This study enhances understanding the role of online entertainment in shaping consumer behavior. It also provides recommendations for companies to advance their networking capabilities, marketing credibility, and customer relationship management in cardigan shopping industry. Moreover, this study emphasizes the need for enterprises to prioritize the content quality and its impact on behavioral engagement to create value, and contribute valuable insights to the existing literature.